Lattice rotations during channel-die compression at high strain rates in copper single crystals of {110}<112>, {112}<111> and {123}<634> orientations. Issue 1 (1st July 2022) - Mania, I; Paul, H; Chulist, R
Abstract: The microstructure and texture evolutions of high purity copper single crystals of Br(1-10)[112], C(112)[11-1] and S(346)[63-5] initial orientations were investigated to evaluate the influence of high strain rate on the intensity of twinning and shear banding. The samples were deformed up to 60% in a channel-die at a strain rate of 7 × 10 5 s -1 using explosive energy to propel the punch. The microstructure was characterized by optical microscopy as well as scanning and transmission electron microscopy. High strain rates of deformation of C and S-oriented single crystals lead to massive deformation twinning. Despite the identification of three families of compact clusters of twins of two generations, the microstructure and texture of both single crystals are practically dominated by the twinning on only one co-planar slip plane. The common rotation of twin-matrix layers, within the narrow area, combined with deformation twinning in the re-oriented matrix are responsible for final SB texture formation. This mechanism contributes to the formation of orientations from the neighborhood of the {110}<100> orientation. The {110}<112> orientation, stable during deformation in channel-die in the range of 'conventional' strain rates, lost its stability giving rise to intense twinning and deformation bands across the deformed specimen.